Critical cardiac care in children: looking backward and looking forward - Checchia, Paul A. (Transl Pediatr, 2016)
The growth of Pediatric Cardiovascular Intensive Care as a subspecialty has been incredible. Outcomes have improved, care delivery has matured, and research has made advances. Within this review, we take the opportunity to examine the subspecialty’s past accomplishments with pride, take stock in its current state, and look forward with excitement to its future. While outcomes in general have improved dramatically, we must always be aware of the outcomes that matter to families and patients. Additionally, we must constantly ask ourselves to improve. Research into neuroprotection and individual therapeutic strategies based in genomic medicine provide the next opportunity for the subspecialty to improve.